O uso do Tangram no ensino e aprendizagem de geometria plana no ensino fundamental II - SILVA, Renato Cardoso da (2022)
The general objective of this work was to analyze the use of Tangram as a pedagogical strategy in the teaching and learning of mathematics for Elementary School II. The specific objectives were: to characterize and define Tangram; to observe Tangram as a teaching resource and to relate Tangram and the teaching of mathematics (geometry) in elementary school II. A bibliographical, descriptive and qualitative research was carried out that sought to identify the learning of applied mathematics in elementary school II, using the Tangram. in books, magazines, scientific articles and academic productions, resulting in important points for the study and discussion of the theme. Thus, from the authors consulted, it was observed that the use and applicability of Tangram in the teaching and learning of mathematics in elementary school II proved, according to the experiences of teachers in the classroom, in addition to being playful, valuable to awaken a greater stimulating logical and mathematical reasoning, as well as contributing to the associability of students, who, working in groups, can help each other, clarifying issues and making collective decisions. Thus, it is understood that the use of Tangram in elementary school II is relevant for the learning of Mathematics students.